Quality of life in the elderly in a stretching program - Anacleto, Geovana Mellisa Castrezana (2017)
ABSTRACT: The aim was to evaluate the quality of life of the elderly before and after the intervention. Twenty-one elderly (mean 65.71 years, ± 5.08) participated in a stretching program and WHOQOL-Bref and WHOQOL-Old were used for evaluation. The four dimensions of WHOQOL-Bref showed improvement in indicators, as well as the dimensions of WHOQOL-Old: Past, Present and Future Activities, Social Participation, and Intimacy. It is concluded that there is evidence that stretching type physical activity seems to be beneficial for the studied population.Keywords: Exercise; Stretching; Elderly.